The Eid Tradition Ride Pedicab the Community in Sungai Tiung Cempaka Banjarbaru Village 1975-2022 - Mawaddah, Siti; Subroto, Wisnu; Effendi, Rusdi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The Eid tradition ride pedicab has the potential to become a tourism object based on local culture and wisdom which is quite promising. However, in reality, the local government is not very supportive of introducing it to the general public. The presence of pedicab driver, bentor, delman, and odong-odong from Martapura and native residents who participated in enlivening the Eid day. The aim of this research is to analyze the background to the emergence and impact of the Eid tradition ride pedicab in the community in Sungai Tiung Cempaka Banjarbaru Village from 1975-2022 on the socio-economic life of the surrounding community. The method used is a historical method consisting of heuristics, criticism, interpretation, and historiography. This Eid tradition ride pedicab began to be held in 1975s and had a positive or negative impact on the socio-economic life of the surrounding community.